Applications of ferrocement as a low cost construction material in Malaysia - Abang Ali, Abang Abdullah (International Ferrocement Information Center, 1995)
The efficient use of alternative building materials and technology, appropriate to the local needs of a country must be studied and developed in order to assist the country in sustaining its building activities. Ferrocement, as a relatively new construction material in Malaysia, is slowly gaining acceptance. Various applications of ferrocement as a low cost construction material in the country is discussed.